2019
DOI: 10.5194/amt-2019-229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isotopic characterization of nitrogen oxides (NO<sub>x</sub>), nitrous acid (HONO), and nitrate (NO<sub>3</sub><sup>−</sup>(p)) from laboratory biomass burning during FIREX

Abstract: 1 2 New techniques have recently been developed to capture reactive nitrogen species for 3 accurate measurement of their isotopic composition. Reactive nitrogen species play 4 important roles in atmospheric oxidation capacity (hydroxyl radical and ozone formation) 5 and may have impacts on air quality and climate. Tracking reactive nitrogen species and 6 their chemistry in the atmosphere based upon concentration alone is challenging. Isotopic 7 analysis provides a potential tool for tracking the sources and ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…Interference trials indicate that NO 2 • was not detectable on the NaCl denuder extracts; however, significant amounts of NO 2 – were collected on Na 2 CO 3 coated denuder extracts, indicating a slight interference associated with NO 2 • collection (I = 2.2 ± 0.1%) (Figure b). This value is consistent with previous reports of NO 2 • collection on Na 2 CO 3 denuders that have indicated a collection amount ranging between 1 and 7% of total NO 2 • . While the NaCl denuder extracts indicated no significant NO 2 – , there was a detectable and consistent collection of NO 3 – (1 ± 0.1 ppb v ). Neither NO 2 – nor NO 3 – were detected on NaCl denuders when only flowing N 2 .…”
Section: Resultssupporting
confidence: 91%
“…Interference trials indicate that NO 2 • was not detectable on the NaCl denuder extracts; however, significant amounts of NO 2 – were collected on Na 2 CO 3 coated denuder extracts, indicating a slight interference associated with NO 2 • collection (I = 2.2 ± 0.1%) (Figure b). This value is consistent with previous reports of NO 2 • collection on Na 2 CO 3 denuders that have indicated a collection amount ranging between 1 and 7% of total NO 2 • . While the NaCl denuder extracts indicated no significant NO 2 – , there was a detectable and consistent collection of NO 3 – (1 ± 0.1 ppb v ). Neither NO 2 – nor NO 3 – were detected on NaCl denuders when only flowing N 2 .…”
Section: Resultssupporting
confidence: 91%
“…Akagi et al observed Δ H ONO/ΔNO x molar ratios spanning from 0.16 to 0.33 pptv pptv –1 in South Carolina biomass burning plumes. Chai et al determined an overall range of HONO/NO x ratio from 0.13 to 0.53 pptv pptv –1 for fresh emissions of 20 laboratory fires of different fuels. The laboratory studies by Burling et al found the fire-integrated molar emission ratios of HONO relative to NO x ranged from approximately 0.03 to 0.20 pptv pptv –1 , with higher values observed for southeastern fuels, while later airborne measurements from prescribed burning in southwestern U.S. by Burling et al revealed systematically higher Δ H ONO/ΔNO x molar ratios spanning from 0.077 to 0.22 pptv pptv –1 .…”
Section: Resultsmentioning
confidence: 99%
“…At combustion temperatures over 1000 K, increased fuel rank tends to produce more HCN, while decreased fuel rank favors NH 3 formation. These pyrolysis products then undergo further in-flame processing in the flaming stage. , It is hypothesized that HONO emission results from conversion of NO or NO 2 in series depending on temperature in the vicinity of the flame, where fast oxidations of HCN and NH 3 also occur. , Thus, HONO emissions are expected to anticorrelate with HCN and NH 3 , as they are intermediate products that are being oxidized in the flame chemistry, while HONO emissions are expected to correlate with MCE and NO x , corresponding to higher combustion temperatures which favor more oxidized nitrogen. MCE ranged from 0.86 to >0.94 in WE-CAN, suggesting some of the fire to fire variation in our reported ERs results from burning conditions alone.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify the potential sources of nitrate aerosols, the δ 15 N-NO 3 – values in ambient samples and δ 15 N values in NO x (δ 15 N-NO x ) from various emission sources must serve as input in the SIAR model. Here, the δ 15 N-NO x values of emission sources were obtained from those reported in the literature studies. Vehicle emission and coal combustion are well-known important sources of atmospheric NO x . , In addition, BB (e.g., open burning for agricultural waste and weeds to obtain land for sowing) and biogenic soil emission also contributed a part of atmospheric NO x . , Consequently, four emission sources mentioned above were considered in apportioning the emission sources of nitrate aerosols at QOMS. Table S1 lists the δ 15 N-NO x values in the four emission sources used in the current study.…”
Section: Methodsmentioning
confidence: 99%